The manufacture of honeycomb cores using Fused Deposition Modeling - David Pollard (Taylor & Francis Group, 2017)
Sandwich panels are used in many industries for the advantageous properties of high stiffness, good strength to weight ratio, and impact resistance. This paper investigates properties of thin-walled cores manufactured through Fused Deposition Modeling (FDM); a process which, through a wider design space, could improve the functionality of sandwich panels. The bond strength between the layers of thin walls manufactured through FDM was evaluated through tensile testing. To measure the effect of modified manufacturing speeds, wall thicknesses were varied through the flow rate and nozzle speed. Honeycomb cores using FDM were produced with different toolpaths, and compared with an example of an industry standard Nomex honeycomb core. During tensile testing, thick-walled FDM components exhibited a more ductile failure with a lower yield point when compared to thinner specimens. The ultimate tensile stress remained constant across samples within each of the tested ABS and PLA polymers used. Honeycomb cores produced using FDM were found to have a higher compressive failure force than Nomex honeycomb, and a lower specific strength. The force–displacement curves of compressive failure show a ductile response for thick specimens, consistent with the previous result. These results, combined with the increased flexibility of additive manufacture technologies, could provide a method of manufacturing high strength cores with complex geometry.